Konsumsi Program Survival Show dan Pengaruhnya dalam Third Language Vocabulary Acquisition Bahasa Korea - Meidina R, Irvanti Sufa; Cahyono, Rudi (Buletin Riset Psikologi dan Kesehatan Mental, 2023)
This research is a preliminary study to see the effect of survival show program consumption on Korean language third language vocabulary acquisition. The study used a one-way pre-test post-test design with 10 participants (N=10) aged between 18 and 24 years old currently studying Korean autodidactly as their third language. The survival show program used in this experiment is the 5th episode of the show "Produce 101 Season 2". Then, the researcher tested participants' Korean third language vocabulary acquisition with a set of Korean vocabulary tests. The collected data was then analyzed using the Wilcoxon technique. This research found that The survival show program could significantly increase participants' Korean third language vocabulary acquisition (Z=-4.089, p=0.0001). The result shows that the survival show program could be an effective medium for increase Korean third language vocabulary acquisition autodidactly.